Absolute geostrophic velocity inverted from World Ocean Atlas 2013 (WOAV13) with the P‐vector method. (19th January 2016) - Chu, Peter C.; Fan, C. W.
Abstract : The World Ocean Atlas‐2013 (WOAV13) dataset comprises 3D global gridded climatological fields of absolute geostrophic velocity inverted from WOA13 temperature and salinity fields using the P‐vector method. It provides a climatological velocity field that is dynamically compatible to the WOA13 ( T, S ) fields. The WOAV13 has the same spatial resolution and temporal variation (annual, monthly, seasonal) as WOA13 ( T, S ) fields, but does not cover the equatorial zone (5°S–5°N) due to the geostrophic balance being the theoretical basis for the P‐vector inverse method.